191k views
0 votes
Simplify: (3 + 4i) + (2 - 3i) - (5 - 6i)

2 Answers

5 votes
The answer is: " 7 i " .
________________________________________________________
Step-by-step explanation:
________________________________________________________
(3 + 4i) + (2 - 3i) - (5 - 6i) =

(3 + 4i) + 1(2 - 3i) - 1(5 - 6i) ; ← Note that the coefficient, "1" is implied;
since any value, multiplied by "1" , results in that same value.
_____________________________________________________________
Note the "distributive property" of multiplication:
_____________________________________________________________
a(b + c) = ab + ac ;

a(b – c) = ab – ac .
_____________________________________________________________
We have:

(3 + 4i) + 1(2 - 3i) - 1(5 - 6i) ;

Start with:

" + 1(2 - 3i) " = (1*2) - (1*3i) = 2 - 3i ;

Then, we examine:

" - 1(5 - 6i) " = (-1*5) + (-1 * -6i) = -5 + (+6i) = -5 + 6i ;
______________________________________________________________
And we rewrite the entire expression:
______________________________________________________________
3 + 4i + 2 - 3i - 5 + 6i ;

Combine the "like terms" ; as follows:

3 + 2 - 5 = 5 - 5 = 0 ;

4i - 3i + 6i = 1 i + 6i = 7 i ;

0 + 7i = 7i .
_______________________________________________________
The answer is: " 7 i " .
_______________________________________________________
User Radka
by
5.6k points
6 votes
(3 + 2 - 5) and (4i - 3i + 6i)
= 0 + 7i
User Bangkokian
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.